Evaluasi Rigless Plug & Abandonment: Sebuah Studi Kasus - Cindy Clara Afrisca; Ganesha Rinku Darmawan (Jurnal Nasional Pengelolaan Energi MigasZoom, 2020)
Oil was explored and found by Royal Dutch (Shell Group) geologist in early 1900. And since Indonesia’s independence, development in oil and gas projects was able to put Indonesia as one of major oil exporter country with daily production above 1 Million barrel per day in 1970 – 1990. With time as fields become mature, some of the fields have come to the end of its life cycle, where mostly 70% of Indonesia total old oil wells will have no economic value and has to be permanently Plug and Abandonment (P&A) as ruled by the government. It’s part of decommissioning an entire field with environmental preservation which called Abandonment and Site Restoration (ASR). As P&A will impact operating company investment as outlined in Ministry of Energy and Mineral Resources (ESDM) No. 15, 2008, efficient P&A operation should be evaluated to ensure proper planning and executions. The subject of evaluation is X well located onshore at Y Field, Java, Indonesia. P&A operation with multiple cements plugs as barriers to ensure no fluids migrations from one formation to others, or to surface. Evaluation between workover rig and rigless P&A operation with coiled tubing unit (CTU) and electric line (E-line) will be presented in this paper to value the expenditures and achieving the result as standardize by the government with accordance of operating company standard. Results show that rigless operation with CTU is the preferable solution, which lead to cost effective operation. Rigless operation with CTU saves 27% of P&A operations even tough with longer operation days.